Transformative Pedagogy of Multiliteracies and the Challenges of Cultural Constraint in Indonesia - Siregar, Yuniar Dwi Ansari; Ramadhan, Rizki (English Education Department STKIP Al Hikmah Surabaya, 2018)
This paper intends to see the literacy pedagogy in Indonesia from the point of view of transformative pedagogy of multiliteracies (Cope and Kalantzis, 2009). It can be argued that the educational change in Indonesia is moving away from the overt instruction (conceptualizing) orientation of literacy pedagogy to the transformed practice (applying) orientation of literacy pedagogy. Beside the convincing argument that this change is needed, there are several challenges in applying this practice in the classroom and one of it is the cultural constraint. This paper will try to describe Indonesian culture of learning as the basic argument of cultural constraint challenges and as an attempt to see the literacy movement in Indonesia from the sociocultural perspective of educational change. This description will then help framing the implications both for teachers as the agent of change and for government as on how to manage the change. Data and support written in this article are from secondary sources as this article intends to be a literature review. Suggestions coming from the literature discussed that a ‘collaborative work culture’ (Fullan & Hargreaves, 1992) is the solution of the challenge in implementing a transformative pedagogy of multiliteracies in Indonesian context.